Design and Development of a Programmable Logic Controller (PLC) Trainer Kit as a Practical Support Tool for the Programmable Logic Control Course - Wahab, Abdul; Djaohar, Mochammad; Yuninda, Nur Hanifah (Journal of Electrical Vocational Education and Technology, 2024)
The rapid development of modern industries increasingly relies on automation systems to improve product quality, shorten production time, and reduce human labor costs. One of the technologies used in automation systems is the Programmable Logic Controller (PLC), which has replaced conventional control systems. To meet industry demands, students in the Electrical Engineering Education Program at Universitas Negeri Jakarta (UNJ) are expected to have skills in operating and programming PLCs. However, based on observations, students' understanding of PLC materials remains low, and the laboratory's supporting facilities for PLC learning are still limited. This research aims to develop a PLC Trainer Kit and its corresponding Jobsheet as a Practicum Support Tool in the Programmable Logic Control course. The development method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research results show that the developed PLC Trainer Kit obtained a feasibility score of 97.3% from material experts, 89% from media experts, and 94% from student trials. Thus, it can be concluded that this PLC Trainer Kit is highly suitable as a learning aid in the Electrical Engineering Education Program at UNJ. This study is expected to contribute to improving students' understanding of PLCs and facilitating more interactive and applicable learning.